Historical study on the development of the weaving motif of Bima, West Nusa Tenggara, Indonesia - Ramadhan, Nursyahri; Karyono, Tri; Soeteja, Zakarias Sukarya (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
This study aims to trace the early history of the Bimanese to identify the weaving and its 10 motifs defined in the Bima Land Customary Law as part of the Bima ethnic characteristics. The study used a qualitative approach with data triangulation (observations, interviews, and documentation). The research result showed that the activity of spinning yarn was known by the Bimanese before the expedition of Sang Bima to the land of the rising sun (Satonda Island, a volcanic area on Sumbawa Island), which became the ancestors of the Bimanese. They used weaving to make clothes, using similar procedures of Javanese weaving. Initially, the motifs of Bimanese woven were only in the form of stripes and rectangles, but the acculturation with Javanese culture during the heyday of Majapahit influenced the development of motifs in the Bima Kingdom during the 11-13th centuries. Subsequently, there was also acculturation with Bugis and Malay culture after the Bima Kingdom turned into a Sultanate. For instance, in choosing a leader, the Bima people should adopt the principle in the nggusu waru (octagonal) motif or that the Bima people must always bring benefits and noble characteristics like the scent of a flower in the Satako flower motif.